Stochastic Optimal of Integrated Energy System in Low-Carbon Parks Considering Carbon Capture Storage and Power to Hydrogen - Jiangnan LI; Renli CHENG; Baorong ZHOU; Jiajin LIU; Tian MAO; Wenmeng ZHAO; Tao WANG; Guanglei HUANG; Yinliang XU (Zhongguo dianli)
In response to the needs of zero-carbon transformation in industrial parks, a multi-energy complementary technology combination of "new energy power generation + hydrogen energy storage" and "thermal power + carbon capture" has been established. Considering add the corresponding emission reduction of hydrogen vehicles to carbon trading and the direct sale of hydrogen energy to hydrogen vehicles, the system aims to achieve optimal economy and low-carbon performance. Besides, the system quantifies low-carbon benefits through the consumption rate of renewable energy, new energy abandonment rate and emission reduction of hydrogen vehicles. The results show that the system can not only increase the consumption of wind and solar new energy, reduce carbon emissions, but also reduce operational costs. The system can verify the feasibility of the transformation of the zero-carbon park.